G-107 Enzymatic manipulation of antibody Fc-mediated effector functions. (January 2016) - Sundberg, Eric
Abstract : In order to evade host immune mechanisms, many bacteria secrete immunomodulatory enzymes. Streptococcus pyogenes, one of the most common human pathogens, secretes a large endoglycosidase, EndoS, which removes carbohydrates in a highly specific manner from IgG antibodies. This renders antibodies incapable of eliciting[LINE SEPARATOR]host effector functions through either complement or Fc g receptors, providing the bacteria with a survival advantage. On account of this antibody-specific modifying activity, EndoS is currently being developed as a promising injectable therapeutic for autoimmune diseases that rely on autoantibodies. Additionally, EndoS is a key enzyme used in the chemoenzymatic synthesis of homogenously glycosylated antibodies with tailored Fc g receptor-mediated effector functions. Despite the tremendous utility of this enzyme, the molecular basis of EndoS specificity for, and processing of, IgG antibodies has remained poorly understood. We have recently determined the X-ray crystal structure of EndoS. Based on this structure, we rationally designed chimeric endoglycosidases in which we exchanged the glycosidase domain of EndoS with that of EndoF1 in order to create unique enzymes for customized glycan remodeling on IgG antibodies. This novel glycoprotein engineering strategy for constructing chimeric endoglycosidases that are able to manipulate the glycan composition on IgG antibodies provides new opportunities to engineer antibodies with unique glycan compositions for therapeutic applications.